SHERPA-city: A web application to assess the impact of traffic measures on NO2 pollution in cities. (January 2021) - Degraeuwe, B.; Pisoni, E.; Christidis, P.; Christodoulou, A.; Thunis, P.
Abstract: This paper presents SHERPA-City, a web application to assess the potential of traffic measures to abate NO2 air pollution in cities. The application is developed by the Joint Research Centre. It is freely available (https://integrated-assessment.jrc.ec.europa.eu ) and allows the user to perform a fast screening of possible NO2 abatement measures addressing traffic in European cities. SHERPA-City results depend on the quality of the default input data. It is therefore important to stress that the SHERPA-City default traffic flows, emission factors, fleet composition, road network topology, NO2 pollution from other sources and meteorological data are based on EU-wide datasets that may not always represent perfectly a particular local situation. This is why the SHERPA-City allows the default data to be substituted by local data, to better reflect local features. This tool must be considered as a first step in exploring options to abate NO2 air pollution through transport measures. The final decisions should be based, wherever possible, on full-scale modelling studies incorporating local knowledge. Graphical abstract: Image 1 Highlights: A free user-friendly web application to evaluate the impact of traffic measures on NO2 concentrations in European cities. EU wide default traffic data and emission factors are provided. Possibility to upload own traffic data and emission factors. A case study on Madrid Low Emission Zones demonstrates the key features of the tool.